(untitled) (Journal of Applied Oral Science, 2021)
Objective: Ameloblastoma is a representative odontogenic tumor comprising several characteristic invasive forms, and its pathophysiology has not been sufficiently elucidated. A stable animal experimental model using immortalized cell lines is crucial to explain the factors causing differences among the subtypes of ameloblastoma, but this model has not yet been disclosed. In this study, a novel animal experimental model has been established, using immortalized human ameloblastoma-derived cell lines. Methodology: Ameloblastoma cells suspended in Matrigel were subcutaneously transplanted into the heads of immunodeficient mice. Two immortalized human ameloblastoma cell lines were used: AM-1 cells derived from the plexiform type and AM-3 cells derived from the follicular type. The tissues were evaluated histologically 30, 60, and 90 days after transplantation. Results: Tumor masses formed in all transplanted mice. In addition, the tumors formed in each group transplanted with different ameloblastoma cells were histologically distinct: the tumors in the group transplanted with AM-1 cells were similar to the plexiform type, and those in the group transplanted with AM-3-cells were similar to the follicular type. Conclusions: A novel, stable animal experimental model of ameloblastoma was established using two cell lines derived from different subtypes of the tumor. This model can help clarify its pathophysiology and hasten the development of new ameloblastoma treatment strategies.